Effects of Soil Physico-Chemical Properties on Plant Species Diversity Along an Elevation Gradient Over Alpine Grassland on the Qinghai-Tibetan Plateau, China - Han, Wangya; Chen, Li; Su, Xukun; Liu, Dan; Jin, Tiantian; Shi, Songlin; Li, Tao; Liu, Guohua (Frontiers in Plant Science, 2022)
Elevation gradient can reflect the effects of soil physico-chemical properties on plant species diversity. Alpine grassland on the QTP has suffered from a serious decline in plant species diversity. In this study, we investigated 112 sites recording plant community characteristics and collecting soil samples along an elevation gradient (3,500-5,200 m asl) in alpine meadow on the QTP. We analyzed the effects of soil physico-chemical properties on plant species composition and diversity by canonical ordination and spatial regression along an elevation gradient. The results showed that species richness of the overall plant communities decreased with the increasing elevation, and the Simpson dissimilarity index (βsim) had a maximum at low elevation (3,500-4,000m) with the value of 0.37.. Soil available nitrogen content was the primary soil parameter affecting plant species composition and diversity in alpine grassland. The effect of soil available nitrogen content on plant species richness varied at different elevations. For Gramineae plants (G), plant species richness declined with the increase in soil available nitrogen content at low elevation (3,500-4,000m), but rose at middle elevation (4,000-4,500m). Soil available nitrogen content had a more significant limiting effect on species richness at high elevation (> 4,500m). These findings increase our understanding about the drivers of plant species diversity changes in alpine grassland on the QTP, and will provide insights into grassland restoration and sustainable management.